Atezolizumab with bevacizumab and nonplatinum chemotherapy for recurrent ovarian cancer: final results from the placebo-controlled AGO-OVAR 2.29/ENGOT-ov34 phase III trial : gynecologic cancer - Harter, Philipp; Marmé, Frederik; Redondo, Andrés; Reuss, Alexander; Lindemann, Kristina; Kurzeder, Christian; Van Nieuwenhuysen, Els; Marth, Christian; Pietzner, Klaus; Ray-Coquard, Isabelle; Garcia-Duran, Carmen; Jonuskiene, Goda; et al. (Journal of clinical oncology, 2026)
Purpose - To evaluate atezolizumab combined with bevacizumab and non-platinum-based chemotherapy for recurrent ovarian cancer. - Methods - The double-blind randomized phase III AGO-OVAR 2.29/ENGOT-ov34 trial (ClinicalTrials.gov identifier: NCT03353831) enrolled patients with first or second relapse of ovarian cancer ≤6 months after completing platinum-based chemotherapy (or third relapse regardless of treatment-free interval). PD-L1 status was tested centrally (VENTANA SP142 assay) in recent (<3 months) biopsies before random assignment. All patients received bevacizumab and investigator-selected chemotherapy (once weekly paclitaxel or pegylated liposomal doxorubicin) until disease progression or toxicity, plus either atezolizumab 840 mg or placebo once every 2 weeks until progression (maximum 2 years), randomly assigned 1:1, and stratified by number of previous lines, planned chemotherapy, previous bevacizumab, and PD-L1 status. Primary end points were overall survival (OS) and progression-free survival (PFS) in the intention-to-treat population. - Results - Among 574 patients randomly assigned between September 2018 and July 2022, 72% were bevacizumab-pretreated, 36% had received three previous treatment lines, 26% had PD-L1-positive tumors, and 54% received paclitaxel with study therapy. After 418 patients had died, the hazard ratio for OS was 0.83 (95% CI, 0.68 to 1.01; P = .06; median 14.2 months with atezolizumab and 13.0 months with placebo) and the hazard ratio for PFS was 0.87 (95% CI, 0.73 to 1.04; P = .12; median 6.4 v 6.7 months, respectively). OS hazard ratios were similar regardless of PD-L1 status. Grade ≥3 adverse events occurred in 72% of atezolizumab-treated and 69% of placebo patients. - Conclusion - Combining atezolizumab with bevacizumab and chemotherapy did not significantly improve OS or PFS in patients with recurrent ovarian cancer ineligible for platinum. The safety profile was as expected from previous experience with these drugs.
Online veröffentlicht: 3. Dezember 2025
Gesehen am 26.02.2026